Improving Patient Safety through Effective SBAR Communication - Efendi, Zulham; Adha, Dedi; Isesreni (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Patient safety is a major challenge in health services that can occur due to ineffective communication between health workers. Effective communication used by nurses is SBAR communication, which is effective communication that can reduce errors. In Indonesia in 2021 there were 145 patient safety incidents, In 2023 the implementation of patient safety at Dr. Rasidin Hospital was 49%. This study aims to determine the relationship between SBAR communication and patient safety in Inpatient Care at Dr. Rasidin Hospital. The type of research used is quantitative with a cross-sectional approach. The study was conducted at Dr. Rasidin Hospital with data collection carried out on March 6-7, 2025. The total sampling technique, 43 respondents were obtained, Analysis using the Chi-Square Test. The results showed that SBAR communication was 51.2% effective and patient safety was 51.2% good. Statistical analysis showed a relationship between SBAR communication and patient safety (p = 0.022). It is expected that Dr. Rasidin Hospital will pay attention to the quality of nursing services based on the principles of nurse SBAR in order to improve patient safety in the future